VD_FINDINFO Jug / 2011 / 289 vom 31. Mai 2011 - VD Tribunal cantonal (2011)
TORT MORAL, PARTIE CIVILE, LOI FÉDÉRALE SUR LA CIRCULATION ROUTIÈRE, LÉSION CORPORELLE PAR NÉGLIGENCE | 47 CO, 125 al. 1 CP, 29 al. 2 Cst., 62 al. 1 LCR